Scale to Measure the Utilization of Farm Implements by the Farmers - Patil S.D. and S. B. Shinde, (Indian Journal of Extension Education, 2016)
Farm mechanization helps to enhance the overall productivity and production with the lowest cost of production. In thecontext of increasing commercialization of agriculture, mechanization is very important. But all the farmers may notutilize the improved farm implements at the same time and at the same rate. It is very important to know the extent ofutilization of farm implements by the farmers. However, a systematic evaluative study on utilization of farm implementsby the farmers unfortunately has not drawn sufficient research attention which again is due to non availability of a scale tocorrectly measure the farm implements utilization. Hence, an effort was made to construct and standardize a scale tocorrectly measure the utilization of farm implements by the farmers. The study was conducted in Newasa, Rahuri, Karjatand Pathardi tahsils of Ahmednagar district and Pandharpur, Malshiras, Karmala and Mohol tahsil of Solapur district. Themethod of identification of the parameters, framing and scoring of the parameters and relevancy analysis was followed inthe construction of the scale along with testing of its reliability and validity. The scale developed was found to be highlyreliable and valid to measure the utilization of farm implements by the farmers. Also it can be used to measure the extent ofutilization of farm implements by the farmers beyond the study area with suitable modifications if required.